Waste Management System “Kompas Lestari” as the Economic Empowerment Program in Makartitama Village, Peninjauan District, Ogan Komering Ulu Regency - AMALIA, RICHA; Wahyudi, Hangge Daud; Suharyadi; Putra, Erwin Hendra (Prospect Publishing, 2024)
The natural environment has a significant role for human survival, humans, and nature are inseparable. Makartitama Village, Peninjauan Subdistrict, Ogan Komering Ulu Regency also experiences the same problem, namely damage to the natural environment due to waste generation in residential areas. This study aims to determine the impact of the Sustainable Compass Program on people's lives. The research methodology used is qualitative research. Data collection techniques were carried out through in-depth interviews, Focus Group Discussions (FGD), and observations of Kompas Lestari members, Makartitama Village Government, and Makartitama Village Community in general. The case study approach was chosen to understand the problems in the research in depth. The data analysis technique used is an interactive model starting from the data collection stage and continuing with data reduction, data display and the last stage is drawing conclusions. The impact of the program on the environment is the reduction of organic waste in Peninjauan Sub-district thanks to the processing of organic waste in Makartitama Village. This impact can be felt in the economic, welfare, environmental and social sectors. The impact measurement was carried out using the Community Satisfaction Survey (IKM) and Social Return On Investment (SROI) methods.